2022
DOI: 10.3389/fpls.2022.900262
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Mediates Axillary Bud Outgrowth by Improving Nitrogen Assimilation and Transport in Rice

Abstract: Melatonin plays an important role in plant resistance to biotic and abiotic stresses. However, whether melatonin is involved in the regulation of plant architecture, such as the formation of axillary bud outgrowth or tillering, in rice remains unknown. Here, we found that different concentrations of melatonin influenced axillary bud outgrowth in rice, and moderate melatonin concentrations also alleviated the inhibition of axillary bud outgrowth in the presence of high concentrations of basic amino acids lysine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Similarly, it was shown that OsAAP5 expression is up‐regulated by nitrate and ammonium concentrations (Wang et al, 2019). Additionally, it has been reported that OsAAP14 expression levels are regulated by exogenous basic amino acids (Yang et al, 2022). The expression of OsAAP15 is significantly up‐regulated under 0.5–15 mM N treatment (Yang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was shown that OsAAP5 expression is up‐regulated by nitrate and ammonium concentrations (Wang et al, 2019). Additionally, it has been reported that OsAAP14 expression levels are regulated by exogenous basic amino acids (Yang et al, 2022). The expression of OsAAP15 is significantly up‐regulated under 0.5–15 mM N treatment (Yang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CRISPR of OsAAP5 significantly increases tillers by decreasing levels of basic amino acids Lys and Arg (Wang et al, 2019). OsAAP14 overexpression leads to increased tillers in rice subjected to melatonin concentrations (Yang et al, 2022). The response of OsAAP15 negatively influences panicle branching under high nitrogen conditions, affecting the levels of endogenous amino acids Tyr and Val in rice panicles (Yang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…To delve deeper into amino acid transport, ZH11, OsAAP7 OE and C lines were subjected to treatment with 1 mM Fluorescent amino acid Arg, Phe or Lys for 2 h, 6 or 10 h. Subsequently, the rice seedlings were examined using a Chemiluminescence Apparatus (Qinxiang, China), and the fluorescent intensity was quantified utilizing Bandscan [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…OsAAP6 regulates the uptake and distribution of amino acids in rice [ 22 ]. Amino acid transporter OsAAP14 determines bud outgrowth under melatonin treatment, thereby influencing rice tillering and grain yield [ 23 ]. Overexpressing of OsAAP15 in rice enhances both primary and secondary branches in the panicle, attributed to its impact on the concentrations of amino acids Tyr and Val in the rice panicle [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have suggested that amino acid transporters play a fundamental role in the process of organic N recycling [8,11,12]. Moreover, an increasing number of reports indicate that various amino acid transporters are involved in the regulation of plant growth and development and abiotic and biotic stress tolerance [12][13][14][15][16]. In Arabidopsis, overexpressing AtCAT1 decreases the total biomass of soil-grown plants and enhances the resistance to pathogen attack (P. syringae) [12].…”
Section: Introductionmentioning
confidence: 99%